Edukasi Risiko dan Upaya Preventif Penyalahgunaan Narkoba pada Pelajar SMKN 7 Kota Lhokseumawe - Julita, Usti; Masdina, Erna; Gaol, Lasmina Lumban; Elwata, Junaedy (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2024)
Background: Prevention efforts and the impacts caused by drug abuse in the modern era and today's advanced technology remain a priority. This increase is indicated by the increasing number of drug users from various groups, especially students. The aim of community service is to provide counseling or education on the risks and prevention efforts of drug abuse to students at SMKN 7 Lhokseumawe city. Method:This activity uses the socratic method. Data based on the pre-test and post-test were analyzed using descriptive statistical techniques. The activity was held on March 18 2024 at SMKN 7 Lhokseumawe City with a total of 35 male students ranging in age from 15 – 18 years. Results: the results obtained from pre-test data were low knowledge about types of drugs where 20% of students mentioned marijuana, 5% said crystal methamphetamine and 75% had heard of but did not understand drugs. Meanwhile, the post-test results showed that students were able to explain the meaning of drugs with a score of 93 and very low results were not able to explain the signs and symptoms of drug users with a score of 75. Conclusion: the conclusion was that there was an increase in students' knowledge about drugs. This is proven by the fact that 25% of students were able to explain the types of drugs when the pre-test increased to 90% compared to the post-test, with a maximum score of 100, an average score of 80 was obtained.